Glass sword - Aveyard, Victoria (2016)
The electrifying next installment in the Red Queen series escalates the struggle between the growing rebel army and the blood-segregated world they've always known -- and pits Mare against the darkness that has grown in her soul. Mare Barrow's blood is red -- the color of common folk -- but her Silver ability, the power to control lightning, has turned her into a weapon that the royal court tries to control. The crown calls her an impossibility, a fake, but as she makes her escape from Maven, the prince -- the friend -- who betrayed her, Mare uncovers something startling: she is not the only one of her kind. Pursued by Maven, now a vindictive king, Mare sets out to find and recruit other Red-and-Silver fighters to join in the struggle against her oppressors. But Mare finds herself on a deadly path, at risk of becoming exactly the kind of monster she is trying to defeat.Will she shatter under the weight of the lives that are the cost of rebellion? Or have treachery and betrayal hardened her forever?
"Kneel or bleed"--Dust jacket.
Includes excerpts from Queen Song & Steel Scars; novellas set in the world of Red Queen.
Keywords: Teenage girls -- Juvenile fiction; Blood -- Juvenile fiction; Princesses -- Juvenile fiction; Fiction; Young adult fiction